Moving towards health promoting schools: effectiveness of an educational intervention to improve knowledge, attitude and beliefs regarding heart attack, and CPR knowledge in high school students in Lebanon - Mohamad Abdelkhalik; Eliannore Boutros; Khalid Trad; Oulyana Arafat; Mohamad Nihad Alyousfi; Carmel Bouclaous (Frontiers Media S.A., 2024)
BackgroundHealth promoting schools (HPS) prioritize the health of students and community. One important target of HPS is noncommunicable diseases (NCDs), including prevention of heart attacks, due to their burden on healthcare.ObjectiveThis study assesses the effectiveness of an educational intervention to promote knowledge of signs and symptoms, beliefs and attitudes towards heart attack, and promote knowledge of Cardiopulmonary resuscitation (CPR).MethodsThe intervention consisted of a 6-minute educational video between a pre-and post-survey. Among other questions, the survey included the Calgary Charter on Health literacy scale, the acute coronary syndrome response index questionnaire, and items assessing knowledge of CPR.ResultsA total of 401 high school students participated (58.9% females). Few students had adequate baseline knowledge of heart attack symptoms (22%) and CPR (7%). The sample showed moderate level of health literacy (12 ± 2.7). Chest pain was the most identified symptom (95%) while abdominal pain was the least identified (14.25%). The intervention significantly increased knowledge, beliefs and attitudes towards heart attack, and knowledge of CPR (p < 0.001). Following the intervention, 83.2% of students demonstrated sufficient knowledge of heart attack symptoms, and 45% exhibited adequate knowledge of CPR. Variables predictive of better attitude, in other words higher confidence in recognizing and reacting to symptoms of heart attack, included having higher health literacy and prior knowledge of risk factors (p < 0.05). Needing help reading medical instructions sometimes predicted worse belief in their capacity to act if they experienced or witnessed a heart attack [score (p < 0.05)]. It was also predictive of worse attitude towards heart attack (OR = 0.18).ConclusionHigh school students in Lebanon lack appropriate knowledge, attitudes, and beliefs toward heart attack, and lack CPR qualifications. Scale up of this educational initiative, along with training of teachers and school personnel, can be used as part of a holistic HPS program aimed at raising awareness of heart attack and first responder preparedness.